Impact of concrete block bin on wheat storage losses and food security - Chattha, Shakeel Hussain; Che Man, Hasfalina; Lee, Teang Shui; Mirani, Benish Nawaz; Mahadi, Muhammad Razif (International Network for Natural Sciences, 2014)
Farmers in Pakistan face many storage problems leading to huge losses in the stored wheat. It is therefore, utmost important to protect our food reserves and prevent losses caused by pest’s infestation and improper storage management. Wheat grain stored in concrete block bins for 12 months retained germination capacity, weight of 1000 grain and fat/lipid content significantly better than grain stored in traditional bamboo/straw bins. Concrete block bins prevented major damage caused by insects, while grain stored in bamboo/straw bins suffered severe losses. Concrete block bins maintain low temperature and moisture conditions for extended periods of time better than traditional bamboo/straw bins. Thus, concrete block bins have shown potential to positively impact the economy of wheat farmers in tropical climate like Pakistan. Concrete block bins have proven to be a promising solution to reduce deterioration of wheat grain and retain high quality of grain for extended period of time.